Multiple intelligences, creativity and executive functions in project learning in job training - Bedoya Suárez, Luz Carolina
SENA, as an entity of the State in charge of providing job training to all Colombians, frames its formative process in humanistic pedagogy and in active methodologies such as project training. In order to observe how this methodology allows the development of creativity, multiple intelligences and executive functions and which relationship is among the variables, a descriptive, quantitative and correlational study was carried out with a group of 79 apprentices from different programs. of technologist level of the Regional Antioquia. Keywords: executive functions, creativity, multiple intelligences, learning by projects, training for work.